Macrophage Polarization Modulated by Porcine Circovirus Type 2 Facilitates Bacterial Coinfection - Zhang, Wen; Fu, Zhendong; Yin, Hongyan; Han, Qingbing; Fan, Wenhui; Wang, Fangkun; Shang, Yingli (Frontiers in Immunology, 2021)
Polarization of macrophages to different functional states is important for mounting responses against pathogen infections. Macrophages are the major target cells of porcine circovirus type 2 (PCV2), which is the primary causative agent of porcine circovirus–associated disease (PCVAD) leading to immense economic losses in the global swine industry. Clinically, PCV2 is often found to increase risk of other pathogenic infections yet the underlying mechanisms remain to be elusive. Here we found that PCV2 infection skewed macrophages toward a M1 status through reprogramming expression of a subset of M1-associated genes and M2-associated genes. Mechanistically, induction of M1-associated genes by PCV2 infection is dependent on activation of nuclear factor kappa B (NF-κB) and c-jun N-terminal kinase (JNK) signaling pathways whereas suppression of M2-associated genes by PCV2 is via inhibiting expression of jumonji domain containing-3 (Jmjd3), a histone 3 Lys27 (H3K27) demethylase that regulates M2 activation of macrophages. Finally, we identified that PCV2 capsid protein (Cap) directly inhibits Jmjd3 transcription to restrain expression of interferon regulatory factor (Irf4) that controls M2 macrophage polarization. Consequently, sustained infection of PCV2 facilitates bacterial infection in vitro and in vivo. In summary, these findings showed that PCV2 infection functionally modulated M1 macrophage polarization via targeting canonical signals and epigenetic histone modification, which contributes to bacterial coinfection and virial pathogenesis.